Auto-organização, inteligência coletiva e cocriação: fundamentos e estudos de caso - Junqueira, José Carlos (2015)
This study investigates the impact of processes of co-creation in organizations in general. Based on a multidisciplinary approach, case studies were carried out in four companies in order to investigate different levels of awareness and maturity concerning organizational processes. The focus was on two of the basic concepts that involve co-creation, i.e., self-organization and collective intelligence. A general survey presents the theoretical framework of the state of the art in research in self-organization and collective intelligence. It identifies the intersections and common characteristics between these concepts with reference to authors such as Humberto Maturana, Edgar Morin, Pierre Lévy, Manuel Castells, Lucia Santaella, Edward Hutchins, and Venkat Ramaswamy. The aim of the case studies was to find evidence for the awareness of processes of self-organization and the impact of collective intelligence in organizations. The result of this study shows that the importance of co-creation is only beginning to be acknowledged in organizations. It was found that there is still a lack of methodology and metrics. In particular, maturity curves are not yet being used, as they should. More specific studies to develop a methodology and tools for the interpretation of adherence in collaborative processes are needed